2011
DOI: 10.1038/sc.2011.79
|View full text |Cite
|
Sign up to set email alerts
|

Reversible post-pregabalin peripheral edema in a spinal cord injury patient

Abstract: Study design: Case report. Objectives: To report a case of paraplegia with limb edema caused by pregabalin. Setting: Turkish Armed Forces Rehabilitation Center, Ankara, Turkey. Case report: A 40-year-old male patient with T11 paraplegia had the complaint of swelling in both the lower limbs. He had been given pregabalin because of the neuropathic pain in both the lower limbs. At 10 months, the patient has experienced edema in lower limbs. There was severe edema in both legs, ankles and feet, more evident on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Previous evidence relating to the incidence of this prescribing cascade is limited to case reports, meaning the true population‐based incidence of this potentially problematic practice was unknown 14–16 . By conducting a comprehensive cohort study using population‐level data, we addressed this gap and established temporality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence relating to the incidence of this prescribing cascade is limited to case reports, meaning the true population‐based incidence of this potentially problematic practice was unknown 14–16 . By conducting a comprehensive cohort study using population‐level data, we addressed this gap and established temporality.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that pregabalin is associated with a 10% to 15% prevalence of peripheral edema and weight gain, with cases reported both in patients without a previous history of cardiac failure 1,4-6 and with HF. 1,7-10 The mechanism of the development of HF symptoms is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…O processo complexo Fluidos e Eletrólitos envolve a manutenção do equilíbrio entre os fluidos e os eletrólitos do organismo (4) . Devido à imobilidade e/ou à permanência prolongada na posição sentada, é comum a ocorrência de edema periférico em pessoas com LM, caracterizado pelo acúmulo de líquido no espaço intersticial, acometendo, principalmente, os membros inferiores (26) . Diante do exposto, é necessário prevenir e controlar o edema periférico nesses pacientes.…”
Section: Modo Interdependênciaunclassified